Precursor comparisons for the upregulation of nicotinamide adenine dinucleotide. Novel approaches for better aging - Palmer, Raymond D.; Elnashar, Magdy Mahmoud; Vaccarezza, Mauro (Aging medicine, 2021)
Nicotinamide adenine dinucleotide (NAD) is a coenzyme found in every human cell and regulates a number of systems across multiple cellular compartments and tissue types via an endogenous and exogenous influence. NAD levels are demonstrated to decline with age and therefore measures to counteract the waning of NAD have been devised. A number of NAD precursor candidates such as nicotinamide riboside (NR), nicotinamide mononucleotide (NMN), the reduced form of nicotinamide mononucleotide (NMNH), nicotinic acid (NA) nicotinamide (NAM), and dihydronicotinamide riboside (DNR) increase NAD levels in vitro and in vivo. This discussion will focus on the precursors NR, NMN, NMNH, and DNR in the upregulation of NAD. There are many publications on NAD precursors as it has become popular for human consumption in recent years due to its vital importance to the general consumer. However, there is no consensus between researchers and this was the aim of this review, to determine and discuss their areas of agreement versus disagreement, to highlight the gaps in research, and to give recommendations for future work. Bioavailability and potency of NR, NMNH, NMN, and DNR is also examined on the light of the most recent literature. Effects of NAD‐boosting molecules on human physiology. NAD+ boosters have a substantial effect on the well‐being and survival of mammals.